Experimental Study on Effect of Magnetic Field on Flow Dynamics of Iron (III) Oxide (Fe2O3) - Water Based Nanofluid using Taylor Couette Flow Apparatus (Nigerian Journal of Technology, 2022)
Experimental investigation of magnetic field effect on Fe3O4-Water based nanofluid undergoing Taylor Couette flow is of great importance since some lubricating systems are replicas of Taylor Couette flow. In this study several experiments were carried out to investigate the influence of nanoparticle concentration on the vortex dynamics of a water based Newtonian nanofluid formulated from Fe2O3 in the presence and absence of magnetic field. Flow dynamics was studied in relation to flow transition, stability, hysteresis and effect of magnetism on these properties. Flow regimes covered in this study include Circular Couette flow, Taylor vortex flow, wavy Vortex flow and Modulated Wavy vortex flow. Bifurcation parameters are nanoparticle volume fraction, inner cylinder rotating frequency and Reynolds number. Experiments were performed on distilled water and Fe3O4-Water based nanofluid to understand its behavior in Taylor Couette apparatus. Critical Reynolds number, Azimuthal wavenumber and travelling waves frequency was recorded for each nanoparticle volume fraction. Power Spectral Analysis of nanofluid flow was carried out using video data from the experiment. It was observed that critical frequency for various transitions decrease with nanoparticle volume fraction for nanofluid in the presence of magnetic field but an inconsistent pattern was observed for nanofluid in the absence of magnetic field. These results show that magnetic field and nanoparticle volume fraction greatly influence the behavior of the flow.